Water environment quality of Dongyu River and estuary area of Nansi lake (Shandong Province, China) based on the characteristics of diatom community - Shuyu Tong; Liwei Yang; Liyuan Wang; Ran Yang; Shiyue Chen (Journal of Freshwater Ecology, 2023)
AbstractThe Dongyu River is a national site for monitoring the inflow of Nansi Lake, located in the southwest of Shandong Province, China. Water quality has a significant impact on the safety of the South-to-North Water Diversion Project. To investigate the water quality of Dongyu River and the estuary area of Nansi Lake, we collected water samples and surface sediments from Dongyu River and the estuary area in May 2019 and analysed the characteristics of the diatom communities and water quality. The results showed that 23026 diatom shells were identified at 15 sampling points in the study area, belonging to 161 species of 23 genera. The dominant diatom taxa were Cyclotella meneghiniana, Fragilaria fasciculata, Fragilaria ulna, Amphora libyca, and Cocconeis placentula. Redundancy analysis explained 43.2% of diatom change information. The Monte Carlo permutation test showed that NH4+-N and DO were significant environmental factors that affected diatom assembly, explaining 34.78% and 8.38% of the diatom variability, respectively. The results of the biological evaluation showed that the water quality of Dongyu River and the estuary area of Nansi Lake were in a light-medium pollution state. The RDA analysis of the diatom community and principal component analysis showed that the water quality of the middle and lower reaches of Dongyu River was poor. In general, the middle and lower reaches of Dongyu River are severely polluted by agricultural non-point sources and controlling the use of nitrogen and phosphorus fertilisers and the emission of nitrogen-containing organic matter can preserve the aquatic water quality of Dongyu River and the water safety of the East Route of the South-to-North Water Transfer Project.